Socio-spatial inequalities in Sarawak: the role of Sarawak corridor of renewable energy (score) - Echoh, Daniel Ugih; Md Nor, Norizan; Masron, Tarmiji (2015)

(untitled)
The failure of the colonial government to develop the economic sector for this state was due to the adoption of a biased development approach. The biased approach focused on the potential of existing urban areas, and on economic growth oriented rather than distributed growth. Various economic development projects had been implemented since Sarawak became part of Malaysia. As the biggest state in the country with multi-ethnic population, Sarawak definitely needs more strategic development approach and attention from the central government. The Ninth Malaysia Plan has shown that spatial inequality in Sarawak has widened and needs attention. The launching of Sarawak Corridor of Renewable Energy (SCORE) marked the shift to the new approach of development in improving the spatial inequality in Sarawak through regional development strategy. This paper discusses the spatial inequality in Sarawak and explore the potential role of SCORE in regional development.